PENGARUH PERSONAL KNOWLEDGE, TECHNOLOGY LITERACY DAN JOB PROCEDURE TERHADAP KINERJA KARYAWAN PADA DEPARTEMEN IT BANK DANAMON - Chaerul Bachri; Wah yudi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aimed to analyze the influence of Technology, Job Procedure, and Personal Knowledge on Employee Performance. This research is motivated by the understanding of the knowledge management system (KMS) which is increasingly important for an organization. The object of the research is the employe in the IT Department PT Bank Danamon Indonesia. Data collection method used was a questionnaire distributed to respondents based on indicators that represent each variable. The analytical method in this study used descriptive statistics with SPSS tools. The results show that the personal knowledge influency the performance of the employees as 0,387. The Influence of Technology literacy to performance of employees is 0,426. Job procedure to performance of employees is 0,218. Contribution to the influence of personal knowledge, Technology literacy to Job performance of employees is 0.823. It can be concluded that the Technology literacy has dominant influence on performance of employees in the IT Department of Bank Danamon Indonesia.